First presence records of Nothofagus nitida (Nothofagaceae) in Argentina and estimation of its potential distribution area - Mathiasen, Paula; Vidoz, Félix; Valle, Sebastián; Ojeda, Valeria S; Acosta, María Cristina; Ippi, Silvina; Cerón, Gerardo A; Premoli, Andrea C (Bosque (Valdivia), 2017)
Nothofagus nitida is an evergreen tree species considered endemic to the humid forests of Southern Chile. In this study, we inform the finding of N. nitida individuals on the eastern slopes of the Andes in Argentina, expanding its potential geographic distribution range, restricted until now to humid areas west of the Andean range, in Chile. New localities correspond to the south outlet of Menéndez Lake on riverbanks of Río Alerce and Río del Paso Viejo, in Los Alerces National Park, Chubut Province, Argentina. Samples of fresh leaves were collected from five individuals that were considered as putative N. nitida, based on leaf and bark morphology. We performed automated sequencing of the ITS nuclear DNA region, which was previously used to identify different species of subgenus Nothofagus. Four of the obtained DNA sequences corresponded to N. nitida. In addition, we carried out a species distribution model that showed other potential areas of occurrence in Argentina. This finding merits the exploring efforts in other localities at the East of the Andean Range, using as guidance the potential distribution maps in order to determine its current distribution and genetic markers to confirm its presence.